Development of Islamic Religious Education Learning Media Based on Articulate Storyline 3 in High Schools - Idris, Husni; Adawiyah, Rabiatul; Wardhana, Kautsar Eka; Ainii, Qurrotu; Wahid, Muhammad Abdul (SYAMIL: Journal of Islamic Education, 2024)
Islamic Religious Education (PAI) plays a crucial role in developing students' cognitive abilities and character. However, PAI learning is often dominated by lectures, as the content is mostly theoretical and normative. This lack of varied learning media has led to low student engagement. The demand for technological integration requires PAI teachers to utilize technology in their teaching, but many are not equipped to create interactive learning media. This study aims to develop PAI learning media using Articulate Storyline 3 and to assess students' motivation in using this media. The research uses a Research and Development (R&D) method, following Borg & Gall's 10-step model. It was conducted in six high schools in East Kalimantan. Preliminary field testing, involving 30 students, showed the following results: for media, 20.24% rated it very good, 41.67% good, 34.52% adequate, and 3.57% poor; for material, 22.50% rated it very good, 40.83% good, 35.42% adequate, and 1.25% poor; for learning, 28.79% rated it very good, 46.21% good, 23.11% adequate, and 1.89% poor. Similar positive results were found in further field testing. The analysis of learning outcomes using SPSS indicated a significant difference before and after using the media, with a Sig. (2-tailed) value of 0.000. This shows that interactive multimedia enhances students' learning performance.